QUALITY CHARACTERIZATION OF PHULALI CANAL WATER FOR IRRIGATION PURPOSES - Wattoo, M.H. S.; Wattoo, F. H.; Qazi, T. G.; Tirmizi, S. A.; Bhanger, M. I.; Mahar, R. B.; Iqbal, J. (The Nucleus, 2020)
Impact of sewage and industrial effluents on the quality of Phulali canal water for agricultural purpose was monitored while passing through Hyderabad city. Present study is made to monitor pollution parameters like pH, EC, COD, DO, BOD, Fecal coliforms, SAR and some essential elements. The results were then compared with irrigation water standards and national environmental quality standards (NEQs). The values of pH, EC, TDS, and fecal coliforms were found higher with marginal to unsafe hazardous status. Calcium, magnesium and sodium were found higher than potassium and water is found to be poorly suitable for irrigation purposes in the long run.